The Effect of Vitamin E and Selenium, versus Equine Chorionic Gonadotro pin (eCG) on the Reproductive Performance of Synchronized Ewes as Mea sured by Ultrasonography (Indian Journal of Animal Production and Management, 2026)
This study examined the effect of Vitamin E and Selenium, compared to  equine chorionic gonadotropin (eCG), on the fertility of synchronized  ewes as measured by ultrasonography. The objective of this study was to  use ultrasound to assess the effects of Vitamin E and Selenium compared  with those of equine chorionic gonadotropin (eCG) on the reproductive  performance in synchronized ewes. The aim of the study was to increase  fertility or the proportion of multiple pregnancies and to compare the effects  of either hormonal (eCG) or nutritional supplementation (Vitamin E and  Selenium) following estrus synchronization. We used 15 healthy adult ewes, aged 2-4 years. They were divided into three  groups (5 ewes in each group). The ewes were synchronized using intracervical  progesterone-impregnated sponges (Chronogest CR) for 14 days. Following  sponge removal, ewes in the first group were used as untreated controls, ewes  in the second group were given an intramuscular injection of 500 IU eCG,  and ewes in the third group were given an intramuscular injection of 5 ml  of Vitamin E and Selenium. Estrus response was evaluated 24-48 hours after  sponges were removed, and pregnancy was diagnosed by transabdominal  ultrasonography using a 3.5-7.5 MHz probe. It was found that the estrus  response was 100% in all groups. The pregnancy, lambing, and fertility rates  for the control group were 60%, with a multiple lambing rate of 20%. In the  eCG-treated group, pregnancy, lambing, and fertility rates increased to 80%,  with a multiple lambing rate of 60%. The best reproductive performance  was observed in the group treated with Vitamin E and Selenium, where  pregnancy, lambing, and fertility rates reached 100%, while the multiple  lambing rate was 40%. Ultrasonographic examination also demonstrated a  progressive increase in gestational sac size and uterine diameter during early  pregnancy. In conclusion, the findings suggest that the use of Vitamin E and Selenium  after estrus synchronization may enhance reproductive performance and  improve pregnancy outcomes in ewes. Transabdominal  ultrasonography was also found to be useful in early  pregnancy diagnosis, as well as for tracking conceptus  growth in ewes.
Keywords: Estrus synchronization, Ewes, Vitamin E, Selenium, eCG, Ultrasonography, Pregnancy diagnosis, Reproductive performance